Trade Openness Studies In ASEAN-5 And It’s Effect On Unemployment - M Rizki karim amrulloh (Jurnal Pendidikan Ekonomi Indonesia, 2023)
ABSTRACTThe aim of this analysis is to examine the linkages among trade, population growth, interest rates, GDP growth, and unemployment rates in the five ASEAN nations of Indonesia, Malaysia, the Philippines, Singapore, and Thailand between the years 2002 and 2021. This paper is Unique because it simultaneously examines the ASEAN-5 (Founding nations of ASEAN). The source for this research was sourced from the World Bank. The Fix Effect panel data regression model is the most effective model for this research since it can be used to accomplish the goals of the study's descriptive statistical methods, according to the likelihood test. This test demonstrates that the Fix effect model's regression results indicate that the Trade, LnPop, and inflation variables have a significantly negative impact, while GDP growth and wage with unemployment in Asian nations while GDP growth has a positive but not significant. The study demonstrates the necessity of continuing free trade policies.